Early life factors of precocious puberty based on Korean nationwide data - Myeongseob Lee; Junghyun Kim; Haedong Kim; Jaeyong Shin; Junghwan Suh (Scientific Reports)
Abstract Precocious puberty is characterized by early sexual maturation in children before 8 years in girls and 9 years in boys. While puberty is initiated by the activation of the hypothalamic–pituitary–gonadal axis, precise mechanisms triggering the early activation of this axis in children with central precocious puberty (CPP) remain elusive. Here, we aimed to identify variables that may influence the risk of CPP. This retrospective cohort study utilized data from the Korean National Health Insurance Service and National Health Screening Program for Infants and Children and included 43,952 children with CPP and 854,749 controls. Participants were followed up until 2020 for CPP development to determine their height, weight, and head circumference measurements, as well as evaluate their physiological, emotional, cognitive, and social development. The birth weights for boys and girls with CPP were 0.09 and 0.06 kg lower than those of controls, respectively. Breastfeeding rates for children with CPP were lower than those for controls. Children with low birth weights (boys: odds ratio [OR] = 1.71, P < 0.0001; girls: OR 1.30, P < 0.0001) and those who were overweight (boys: OR 1.33, P = 0.0006; girls: OR 1.30, P < 0.0001) or obese (boys: OR 1.60, P < 0.0001; girls: OR 1.14, P < 0.0001) were more likely to develop CPP. Breastfeeding exerted a significant protective effect against CPP in girls (OR 0.95, P = 0.0003). Low birth weight and high body mass index were associated with CPP development.